Four new species of Agave (Asparagaceae, Agavoideae) from southern Mexico - García Mendoza, Abisaí Josué; Franco Martínez, Irma Sonia; Sandoval Gutiérrez, Daniel (Instituto de Ecología, A.C., 2019)
Background and Aims: The genus Agave comprises 159 species and is the eighth most diverse of the Mexican flora. In this work four new species for science are described, result of the exploration of little-known areas from a botanical point of view in the south of Mexico.Methods: As a result of field and herbarium work in the states of Guerrero, Oaxaca, and Puebla, populations of agaves were found whose morphological characteristics do not correspond to previously described species. Following a morphological analysis and a literature review, these are formally described. The conservation status of the four species was evaluated based on the criteria of the NOM-059-SEMARNAT-2010 and the method proposed by the International Union for the Conservation of Nature.Key results: The new species are described and illustrated here, Agave lyobaa, from the subgenus Agave group Ditepalae, and three from the subgenus Littaea, A. gypsicola from the Choritepalae group, and A. quiotepecensis and A. megalodonta from the Marginatae group. For each one, information is provided on distribution, habitat, phenology, possible morphological relationships with other species of the genus, and uses. According to the criteria of the NOM-059-SEMARNAT-2010, the four species are proposed in the Threatened category (A). Based on the method proposed by the IUCN, the first two species are placed in the category Endangered (EN) and the last two in the category Near Threatened (NT).Conclusions: The four species of Agave described here are endemic to Mexico and distributed in the states of Guerrero, Oaxaca, and Puebla. Each is composed of vulnerable populations that require priority conservation actions.